Ross operation early and mid-term results in children and young adults - Oktay Korun; Arif Selcuk; Okan Yurdakök; Hüsnü Fırat Altın; Murat Cicek; Yiğit Kılıç; Sefika Turkan Kudsioglu; Mustafa Orhan Bulut; Numan Ali Aydemir; Ahmet Sasmazel (Anatolian Journal of Cardiology)
Objective: The Ross procedure has been cited as the procedure of choice for young patients requiring aortic valve replacement. However, potential for reintervention requirement in both left and right ventricular outflow tracts can be a source of concern. The aim of the present study was to describe our experience with this procedure. Methods: A retrospective chart review of all the patients who underwent the Ross procedure in a single institution was performed. National death registry records were used for late mortality. Results: Eighteen Ross procedures between May 2003 and May 2018 were performed. The median age of the cohort was 15 [interquartile range (IQR): 12-18] years. The pulmonic conduit was a homograft in 11 patients, Labcor in 5 patients, Contegra in 1 patient, and Medtronic Freestyle Valve in 1 patient. There were three early deaths. The median follow-up of 15 hospital survivors was 11 (IQR: 3–14) years. Any late mortality was not observed. In the two surviving patients with infective endocarditis, there was no recurrent infective endocarditis. Freedom from reintervention was 80% at 8 years and onward. Any risk factors associated with reintervention could not be identified. However, freedom from autograft dilatation at 10 years was 45%. Conclusion: Autograft failure is a potential problem in the long-term follow-up of Ross patients. Freedom from reintervention was satisfactory, and the type of pulmonic conduit did not affect the mid-term outcomes. In patients with infective endocarditis, the Ross procedure has a low recurrence rate, but it might have an increased risk of mortality.